2019
DOI: 10.1075/jicb.17017.dal
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Discourse Functions meet historical competences

Abstract: This paper combines the perspectives of applied linguistics and history education in order to explore the viability of a genuinely non-binary pedagogy for content and language integration. Cognitive Discourse Functions (CDFs) are mapped against the model of historical competences underlying the current Austrian secondary history curriculum. The theoretical analysis shows the performance of CDFs as central to the constitution of historical competences. For the empirical part of the study, two complete didactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This CDF-Construct has been empirically validated for different subjects in a number of MA-theses, summarized in Dalton-Puffer et al (2018). Furthermore, Dalton-Puffer and Bauer-Marschallinger (2019) have shown that the CDF-Construct is compatible with competency-based history education as conceptualized in the Austrian context, both from a theoretical and empirical point of view, indicating that CDFs could work well to operationalize the integration of subject and language learning. Morton (2020), too, argues that CDFs can be used as "building blocks" to foster "focused and principled integration of content, literacy and language" (p. 11).…”
Section: Operationalizing the Integration Of Content And Language: Cognitive Discourse Functionsmentioning
confidence: 86%
“…This CDF-Construct has been empirically validated for different subjects in a number of MA-theses, summarized in Dalton-Puffer et al (2018). Furthermore, Dalton-Puffer and Bauer-Marschallinger (2019) have shown that the CDF-Construct is compatible with competency-based history education as conceptualized in the Austrian context, both from a theoretical and empirical point of view, indicating that CDFs could work well to operationalize the integration of subject and language learning. Morton (2020), too, argues that CDFs can be used as "building blocks" to foster "focused and principled integration of content, literacy and language" (p. 11).…”
Section: Operationalizing the Integration Of Content And Language: Cognitive Discourse Functionsmentioning
confidence: 86%